Discontinuation of modern contraception methods due to side effects and method failure in India: an analysis using reproductive calendar data - Shete, Mahesh R.; Kumar, Prakash; Anand, Enu; Singh, Jayakant; Pradhan, Manas Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Contraceptive discontinuation for reasons other than the desire to get pregnant is a significant public health concern. This study aimed to understand the elaborated role of side effects and method failure behind modern reversible contraception method discontinuation among married women aged 15-49 years in India. Methods: The analysis was based on 142992 episodes of contraceptive use contributed by 90414 married women aged 15-49 years covered in the National family health survey-4 (2015-2016). Multivariate analyses, discontinuation rates using the multiple/single decrement life table and multi-level multinomial competing risk analyses were performed. Results: Discontinuation rate due to side effects within 12 months of use was highest for injectables (14.7%) and lowest for male condoms (3%) and due to method failure, it was highest for male condoms (3%) and lowest among IUD users (1.2%). Compared to women using IUD, those using pills had 2.3 times and 1.6 times the higher hazard of discontinuation due to method failure and side effects, respectively. Conclusions: The discontinuation rate of all selected methods was higher due to side effects than method failure. The high discontinuation rate of many contraceptive methods and the frequency of contraceptive failure suggest the need for strategies to promote improved contraceptive use following method selection. Improved quality of services through proper counselling of the potential contraceptive users would enhance informed choice, thus increasing modern contraception continuation among women in India.